Unveiling the complexities of lung transplantation in situs inversus - Chitaru Kurihara; Taisuke Kaiho; Ankit Bharat (Surgical Case Reports, 2024)
Abstract Background Lung transplantation for situs inverse is considered technically challenging because of the reverse positioning of the organs. By providing a detailed description of the surgical procedure, perioperative care, and post-transplant follow-up, we aim to contribute valuable information to the existing knowledge base. We presented two cases of successful bilateral sequential lung transplantation in situs inverse patients. Case presentation Our first patient was a 28-year-old, non-smoking woman with Kartagener syndrome and advanced bronchiectasis that developed into pneumonia and required repeated hospital admissions. She underwent double lung transplantation. During the lung transplant procedure, venoarterial extracorporeal membrane oxygenation (VA ECMO) support was provided. The recipient’s morphologically right (anatomically left) lung was explanted. The right main bronchus was anastomosed, followed by the pulmonary artery and left atrial anastomoses. Afterward, we proceeded with the left side. Similar to the right side, left pneumonectomy and implantation were performed using the same methods. The duration of VA ECMO support was 147 min with a 328-min ischemic time. Because of the significant size mismatch, nonanatomic lung volume reduction over the right middle and left upper lobes was necessary. The patient had no complications postoperatively and was discharged on post-operative day (POD) 12. Our second patient was a 51-year- old man with scleroderma-associated interstitial lung disease with situs inversus. Bilateral sequential lung transplantation was performed. Similar to case 1, a clamshell incision was made at the fourth intercostal space entry. The patient then received VA ECMO support identical to that in case 1. The total VA ECMO support time was 155 min with 295 min of ischemic time. The patient recovered uneventfully and was discharged on POD 13. Conclusions Lung transplantation for situs inverse can be a viable treatment option without modifying established transplantation procedures.